1998
DOI: 10.1159/000006849
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein A1 Gene Polymorphisms and Risk of Early Coronary Disease

Abstract: Genetic studies have identified polymorphisms at the apolipoprotein (Apo) A1 gene associated with HDL cholesterol and apolipoprotein levels, and a relationship between the severity of coronary artery disease and polymorphisms at the 5′-end of Apo A1 has been also reported. This study was designed to examine the relationship between polymorphism at the Apo A1 gene and the risk of early coronary artery disease. Furthermore, the association of the polymorphism with the classical risk factors was analyzed. A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 19 publications
2
21
1
3
Order By: Relevance
“…This frequency was similar to those observed in Nigerians (10.1%) [36], Japanese (13.5%) [37], other European populations (11.2-15.5%) [13,[38][39][40] and another Brazilian population composed of children (18.1%) [41]. Nevertheless, A allele frequency was lower than in Taiwanese (32%) [42], Spanish (20.3-24%) [17,43,44] and Omani (22%) [45] populations. Our findings also showed a decreased frequency of A allele when compared to an Italian centenarian population, reported as 18.3 and 25.4% for men and women, respectively [7].…”
Section: Discussionsupporting
confidence: 85%
“…This frequency was similar to those observed in Nigerians (10.1%) [36], Japanese (13.5%) [37], other European populations (11.2-15.5%) [13,[38][39][40] and another Brazilian population composed of children (18.1%) [41]. Nevertheless, A allele frequency was lower than in Taiwanese (32%) [42], Spanish (20.3-24%) [17,43,44] and Omani (22%) [45] populations. Our findings also showed a decreased frequency of A allele when compared to an Italian centenarian population, reported as 18.3 and 25.4% for men and women, respectively [7].…”
Section: Discussionsupporting
confidence: 85%
“…Patients with premature atherosclerosis and mutations in genes encoding apoAI associated with deWciency of apoA-I and extremely low concentrations of HDL cholesterol have been described (Karathanasis et al 1987;Matsunaga et al 1991;Ordovas et al 1989). The apoA-1 G75GA polymorphism has been associated with coronary atherosclerosis (Chhabra et al 2005;Reguero et al 1998;Wang et al 1996).…”
Section: High-density Lipoprotein Cholesterol Metabolismmentioning
confidence: 99%
“…Recent epidemiological studies have reported that common ApoA1 polymorphisms influence the levels of HDL-C and triglycerides (TG) (Ordovas et al 1986;Jeenah et al 1990;Pagani et al 1990;Talmud et al 1994;Groenendijk et al 2001b). In addition, several researchers reported associations between ApoA1 polymorphisms and CAD (Karathanasis et al 1983;Ordovas et al 1986;Reguero et al 1998), whereas others found no positive association (Ordovas et al 1991;Marshall et al 1994;Yamada et al 2002). One possible reason for the inconsistencies among previous association studies may be that almost all of these studies considered only a few restriction fragment-length polymorphisms instead of every polymorphism in the ApoA1gene.…”
Section: Introductionmentioning
confidence: 99%